Rubber-Based Industrialisation in Kerala An Assessment of Missed Linkages - Tharian George K Toms Joseph (Economic and Political Weekly January 4-11, 1992, 1992)
Kerala has a near monopoly in the production of natural rubber and yet it consumes only a small proportion of the produce. In fact, the state's NR-based industries are almost entirely confined to NR processing small-scale units with limited linkages. This article attempts to examine the various linkages associated with the rubber plantation industry and assess its future scope